Early detection of reproduction deficits and the compensatory potential of enhancement stocking for vendace, Coregonus albula, fisheries in German lakes. (25th January 2016) - Wanke, T.; Brämick, U.; Mehner, T.
Abstract: Enhancement stocking is a widespread but rarely evaluated practice in German vendace, Coregonus albula L. fisheries, which is precautionarily carried out to buffer yield fluctuations. However, it is assumed that stocking of larval vendace can elevate year‐class strength only in the presence of substantial reproductive deficits, which so far cannot be detected prior to the spring time period when stocking is conducted by fisheries managers. Simple measures for the early quantification of natural reproduction were tested, and the efficiency of larval enhancement stocking in a lake with strong reproduction deficits was analysed. Analysis in four lakes over 3 years revealed a significant positive correlation between standardised catches of vendace larvae caught with pump‐driven illuminated traps in spring and the abundance of young‐of‐year (YoY) vendace in the following autumn, whereas standardised catches of spawners were insufficient to forecast YoY recruitment. In a lake with low natural vendace reproduction, stocked vendace contributed 73–100% of year‐class strength and fisheries yield. Accordingly, enhancement stocking can efficiently compensate for reproduction deficits, and the simple larvae sampling method may facilitate early detection of these deficits, which would allow fisheries managers to respond accordingly through larvae stocking.